2009
DOI: 10.2478/fhort-2013-0124
|View full text |Cite
|
Sign up to set email alerts
|

The effects of triacontanol ‘TRIA’ and Asahi SL on the development and metabolic activity of sweet basil (Ocimum basilicum L.) plants treated with chilling

Abstract: In a potted experiment the influence of foliar application of triacontanol (TRIA) at the concentrations of 0.01; 0.10; 1.00 mg dm -3 , and Asahi SL at the concentrations of 0.1; 0.2; 0.3% on the growth and yielding of plants was studied. Electrolyte leakage, water saturation deficit, contents of proline and chlorophyll a + b in leaves, as well as the maximum quantum efficiency of chlorophyll (F v /F m ) and gas exchange in plants which were treated for five days in temperatures of 15/7°C (day/night) were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 10 publications
8
20
1
Order By: Relevance
“…3). While many investigators have reported that triacontanol significantly improved chlorophyll contents under stress conditions (Krishnan and Kumari, 2008;Borowski and Blamowski, 2009;Naeem et al, 2010;Perveen et al, 2010;. Tria to enhance the diterpenoid production may be attributed to biosynthesis of the compounds that is probably confined in the chloroplasts (Munne-Bosch and Alegre, 2001), tria mediated increment in chlorophyll content in many plants being one of the strong evidences in this regard (Ries, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…3). While many investigators have reported that triacontanol significantly improved chlorophyll contents under stress conditions (Krishnan and Kumari, 2008;Borowski and Blamowski, 2009;Naeem et al, 2010;Perveen et al, 2010;. Tria to enhance the diterpenoid production may be attributed to biosynthesis of the compounds that is probably confined in the chloroplasts (Munne-Bosch and Alegre, 2001), tria mediated increment in chlorophyll content in many plants being one of the strong evidences in this regard (Ries, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Triacontanol (TRIA) enhances growth and yield of various crop species when applied exogenously as foliar spray at various growth stages (Singh et al, 2011). Foliar-applied TRIA ameliorates the negative effects of various abiotic stresses on growth, physiological, and biochemical processes of different plant species, e.g., Erythrina variegata L. seedlings (Muthuchelian et al, 2003), sweet basil (Borowski and Blamowski, 2009), common duckweed (Kilic et al, 2010), soybean (Krishnan and Kumari, 2008), maize (Ertani et al, 2012), canola (Zulfiqar and Shahbaz, 2013), and sunflower (Aziz et al, 2013). Under salt stress conditions, exogenous application of TRIA has been reported to up-regulate genes involved in the photosynthetic process while down-regulating stress-related genes, modulating activities of different metabolic and antioxidant enzymes, enhancing water and mineral nutrient uptake, and stimulating synthesis of various organic compounds through increased nitrogen metabolism (Perveen et al, , 2012Ertani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Perveen et al (2014) 10 mM Triacontanol were sprayed on the leaves in order to more effectively reduce the adverse effects of salt stress on growth, yield, and leaf water relations of wheat plants when applied at the vegetative or vegetative + boot growth stages. This growth substance is also effective to normalize metabolic processes on soyben plants treated with salt stress (Krishnar and Kumari, 2008) and chilling stress on the plants of Ocimum basilicum L. (Borowski and Blamowski. 2009).…”
Section: Introductionmentioning
confidence: 99%